Thematic Pop-Up Book as a Learning Media for Early Childhood Language Development - Sari, Novi Engla; Suryana, Dadan (Program Studi Magister Pendidikan Anak Usia Dini, 2019)
The challenge for early childhood educators to be able to provide a touch of education that is creative, innovative, smart, and fun to develop children's intelligence optimally. This study aims to develop Thematic Pop-Up Book products as learning media for the development of Early Childhood languages. The research subjects were 15 participants in class B6 of Khaira Ummah Islamic Kindergarten in the City. The research and development used data analysis using descriptive statistical analysis techniques. The results of the validity test and the practi-cality of the development of Pop-Up Book media at Khaira Ummah Islamic Kindergarten in Padang City were declared valid by media experts with an average score of 95%. Media Thematic Pop-Up Books, about Healthy and Unhealthy Foodstuffs were also declared valid by material experts with an average score of 95%. The results of the trial of thematic Pop-Up book products in Khaira Kindergarten Islamic Ummah were stated as a practical medium for children with a percentage increase in the test reaching 96%. Based on these results indicate that Pop-Up Book media products get a positive response from children and teachers. Media Pop-Up Book for further research can be used as a medium to improve children's cognitive, and interest in reading. Key Words: Early Childhood Education, Language Development, Thematic Pop-up Book References Arsyad, A. (2017). Media Pembelajaran. PT Raja Grafindo Pursada. Beceren, B. Ö. (2010). Determining multiple intelligences pre-school children (4-6 age) in learning process. Procedia - Social and Behavioral Sciences, 2(2), 2473–2480. https://doi.org/10.1016/j.sbspro.2010.03.356 Berman, R. A. (2018). Language Development and Literacy. Encyclopedia of Adolescence, (October), 2093–2103. https://doi.org/10.1007/978-3-319-33228-4_19 Chaparro-Moreno, L. J., Reali, F., & Maldonado-Carreño, C. (2017). Wordless picture books boost preschoolers’ language production during shared reading. Early Childhood Research Quarterly, 40, 52–62. https://doi.org/10.1016/j.ecresq.2017.03.001 Dato, A., & Radmilovic, V. (2010). Interactive Book With Detachable, Pop-Up Device. Patent Application Publication, 1(19), 20–25. https://doi.org/US 2007/0293118A1 Helmawati. (2015). Mengenal dan Memahami PAUD. Bandung: PT Remaja Rosdakarya. Lin, R. (2012). Creative Thinking for Picture Book Creation. IERI Procedia, 2, 30–35. https://doi.org/10.1016/j.ieri.2012.06.047 Montag, J. L., Jones, M. N., & Smith, L. B. (2015). The Words Children Hear. Psychological Science, 26(9), 1489–1496. https://doi.org/10.1177/0956797615594361 Nazaruddin, M. A., & Efendi, M. (2018). The Book of Pop Up Augmented Reality to Increase Focus and Object Recognition Capabilities for Children with Autism. Journal of ICSAR, 2(1), 9–14. https://doi.org/10.17977/um005v2i12018p009 Obiweluozo, E. P., & Melefa, O. M. (2014). Strategies for Enhancing Language Development as a Necessary Foundation for Early Childhood Education. Journal of Education and Practice, 5(5), 147–155. Retrieved from www.iiste.org Ponitz, C. C., McClelland, M. M., Matthews, J. S., & Morrison, F. J. (2009). A Structured Observation of Behavioral Self-Regulation and Its Contribution to Kindergarten Outcomes. Developmental Psychology, 45(3), 605–619. https://doi.org/10.1037/a0015365 Putra, N. (2011). Research & Development. Jakarta: Raja Grafindo Persada. Rahmawati, D. I., & Rukiyati, R. (2018). Developing Pop-Up Book Learning Media to Improve Cognitive Ability of Children Aged 4-5 Years. Atlantis Press, 249(Secret), 60–69. https://doi.org/10.2991/secret-18.2018.10 Ros, R., & Demiris, Y. (2012). Human Behavior Understanding, 7559, 40–51. https://doi.org/10.1007/978-3-642-34014-7 Safitri, D., & Hartati, T. A. W. (2016). Kelayakan Aspek Media dan Bahasa Dalam Pengembangan Buku Ajar dan Multimedia Interaktif Biologi Sel. Florea, 3(2), 9–14. Sahlan, Asmaun, Angga, & Prastyo, T. (2016). Desain Pembelajaran Berbasis Pendidi-kan Karaker. Yokyakarta: Ar-Ruzz Media. Sari, S. A. (2017). The Development of Pop-up Book on the Role of Buffer in the Living Body. European Journal of Social Sciences Education and Research, 10(2), 213. https://doi.org/10.26417/ejser.v10i2.p213-221 Sudjana, N., & Rivai, A. (2011). Media Pengajaran. Bandung: Sinar Baru Algensindo. Walter-Laager, C., Brandenberg, K., Tinguely, L., Schwarz, J., Pfiffner, M. R., & Moschner, B. (2017). Media-assisted language learning for young children: Effects of a word-learning app on the vocabulary acquisition of two-year-olds. British Journal of Educational Technology, 48(4), 1062–1072. https://doi.org/10.1111/bjet.12472 Wilcox, M.J., M., K.M, Bacon, C. K., & Thomas, S. (2001). Enhancing Children ’ s Language Development in Preschool Classrooms Using Literacy to Target Verbal Language Goals Enhancing Children ’ s Language Development in Preschool Classrooms Encouraging Complex Verbal Reasoning. Arizona. Retrieved from http://icrp.asu.edu Wiyani, & Ardy, N. (2016). Konsep Dasar PAUD. Yokyakarta: Gava Media. Yu, X. (2009). Levels of meaning and children: An exploratory study of picture books’ illustrations. Library and Information Science Research, 31(4), 240–246. https://doi.org/10.1016/j.lisr.2009.07.003